(untitled) (Philology, 2020)
The following text rests upon the academic speech delivered at the official ceremony granting Prof. Dr. Isabel Pires de Lima the honorary title Doctor Honoris Causa by Sofia University “St. Kliment Ohridski” in November 2019. The text discusses the urgent necessity to maintain and develop educational and research practices in the contemporary humanities. By focusing upon the hastiness that dominates contemporary daily grind and manifests in one of the most delicate, widespread and endogenous forms of violence, the article’s debate is centred around the necessity of the academic communities to assert their rights in finding a possible pause, gap, or interval where it is possible to exercise their critical and interpretative abilities. Contemporaneity can be exercised as opposed to the hastiness and robotized hyperactivity that prevents us from indulging in our supreme human authority of saying “no”. Nowadays it is even more pressing to note the immutability of art and its interpretation, filtered through the processes of social interaction, revitalization of knowledge, and recognition of ethical values, while the power of contemporary humanities results from the consideration of those question and values that not only concern us today, but also make a stand against our civil communities. It is the humanities indeed that possess the greatest potential to enrich and direct this grand debate in the right way.